PENERAPAN ENZIM UNTUK PENYAMAKAN KULIT RAMAH LINGKUNGAN - Suyanto Pawiroharsono (Jurnal Teknologi Lingkungan, 2008)
Leather industries contribute significant problems due to the hazard wastes, that threat to environmental sustainability and to human health. The negative impacts are particularly caused by the chemical compounds used in the conventional process of the leather tannery, such as lime, sodium sulphide, chrome, etc. Enzyme is protein compound from biological system, that acts as catalyst (bio-catalyst). Enzyme can be used to replace partly or complete the chemicals used in tannery processes. Recently, micro-organisms are considered a appropriate device to produce enzymes. Furthermore, it is necessary to select potential micro-organisms for enzyme production.“Exolite”, that is first enzyme produced in pilot scale in Indonesia, proved to reduce significantly pollutant in waste of leather tannery industries. Therefore, the development of enzyme industry in Indonesia is needed to be supported.